Attitudes of patients with renal disease on xenotransplantation: A systematic review. (7th March 2023) - DeLaura, Isabel; Anwar, Imran J.; Ladowski, Joseph; Patino, Alejandra; Cantrell, Sarah; Sanoff, Scott
Abstract: Background: Recent years have seen major advancements in xenotransplantation: the first pig‐to‐human heart transplant, the development of a brain‐dead recipient model for kidney xenotransplantation, and the registration of the first xenokidney clinical trial. The attitudes of patients with kidney disease or transplants on xenotransplantation and an assessment of their reservations and considerations regarding the technology are crucial to successful clinical translation and eventual widespread implementation. Methods: This systematic review was registered through PROSPERO (CRD42022344581) prior to initiation of the study and reported using the Preferred Reporting Items for Systematic Review and Meta‐Analyses (PRISMA) guidelines. We included studies that evaluated attitudes towards and willingness to undergo xenotransplantation in patients with end‐stage renal disease (ESRD), including those who had already undergone transplantation. MEDLINE (via Ovid), Embase (via Elsevier), and Web of Science (via Clarivate) were searched from database inception to July 15, 2022 by an experienced medical librarian for studies on xenotransplantation and attitudes. Abstracts and full text were screened using Covidence software and data items regarding study methodology, patient demographics, and attitudes regarding xenotransplantation were extracted using Microsoft Excel. Risk of bias assessments were performed using the Critical Appraisal Skills Programmed and National Institute of Health study quality assessment tools. Results: Of 1992 studies identified, 14 studies met the inclusion criteria. These studies were conducted across eight countries, four in the United States, for a total of 3114 patients on the kidney waitlist or with a kidney transplant. All patients were over 17 years old and 58% were male. Acceptance of a xenotransplant was assessed using surveys in 12 studies. Sixty‐three percent ( n = 1354) of kidney patients reported that they would accept a xenotransplant with function comparable to that of an allotransplant. Acceptance of xenografts with inferior function to allografts (15%) or as bridge organs (35%) to allotransplantation was lower. Specific concerns expressed by patients included graft function, infection, social stigma, and animal rights. Subgroup analyses showed higher acceptance in already transplanted compared to waitlist patients and white compared to Black Americans. Conclusion: An understanding of patient attitudes and reservations is key to the successful execution of the first xenotransplantation clinical trials. This study compiles important factors to consider, such as patient concerns, attitudes regarding practical clinical scenarios for the use of xenotransplantation, and the impact of demographic factors on acceptance of this emerging technology.